How Do Affect the Infusion of Smart Technology and Mindfulness of Tourism SMEs on Competitiveness? - Diaz, Estrella; Esteban, Águeda; Carranza, Rocío; Sánchez-Camacho, Carlos; Martín-Consuegra, David (Springer Proceedings in Business and Economics, 2023)
The purpose of this research is to analyse the effect of the infusion of smart technologies and the mindfulness of tourism small and medium-sized organisations (SMEs) in the use of smart technologies on several aspects related to the companies and their employees. Specifically, its effect on service advantage, value co-creation, employee job satisfaction, employees’ perception of service cannibalisation and competitiveness of tourism companies is analyzed. The total sample obtained was 877 employees/managers of tourism SMEs located in Europe and the United States. The model proposed in the study was estimated with PLS-SEM, a variance-based structural equation modeling statistical technique. The results of the study offer important implications and recommendations to researchers in the tourism field, tourism organisations and destinations on the importance of using smart technologies.
Keywords: infusion; mindfulness; smart technologies; Scopus(2); WOS(2)